Stres Kerja dan Korelasinya dengan Kinerja Perawat di RS X - Putri, Amanda; Tilawah, Koriah; Kadang, Yulta; Hidayat, Wahyu (Universitas Malahayati, 2026)
ABSTRACT Job stress is a factor that can have a significant impact on nurse performance, especially in high-stress environments such as emergency room, ICU, and pediatric ward. Because nurses have a crucial role in health services, their performance is very important to be studied in order to maintain and improve the quality of health services. This study aims to analyze the correlation between job stress and the performance of nurses who work in emergency rooms, ICUs, and pediatric wards. This study applies a correlational method through a cross-sectional approach which was carried out in December 2024. About 41 nurses working in these three units were selected as samples using purposive sampling techniques. Then the data was collected through a questionnaire on work stress and nurse performance, then analyzed with a Gamma test. The study showed that the majority of nurses experienced job stress in the mild category,with 22 respondents (53.7%). Meanwhile, the performance of nurses was mostly good, with 30 respondents (73.2%). Statistical analysis yielded a Gamma value of -0.649, indicating a moderate to strong relationship. In addition, a p-value of 0.030, lower than the significance level of 0.05, shows that the relationship is statistically significant. Based on the results of the study, it can be concluded that job stress has a significant relationship with the performance of nurses in the emergency room, ICU, and pediatric ward. Keywords: Job Stress, Nurse Performance, Emergency Room (ER), Intensive Care Unit (ICU), Pediatric Ward. ABSTRAK Stres kerja adalah sebuah faktor yang bisa sangat berdampak pada kinerja perawat, terutama di lingkungan dengan tingkat stres tinggi seperti IGD, ICU, dan ruang rawat inap anak. Karena perawat mempunyai peran krusial dalam pelayanan kesehatan, performa mereka menjadi sangat penting untuk dikaji guna menjaga hingga meningkatkan kualitas pelayanan kesehatan. Penelitian ini bertujuan menganalisis hubungan antara stres kerja dengan kinerja perawat yang bertugas di IGD, ICU, dan ruang rawat inap anak. Studi ini menerapkan metode korelasional melalui pendekatan cross-sectional yang dilaksanakan tanggal Desember 2024. Sekitar 41 perawat yang bekerja di ketiga unit ini dipilih sebagai sampel menggunakan teknik purposive sampling. Lalu data dikumpulkan melalui kuesioner stres kerja dan kinerja perawat, kemudian dianalisis dengan uji Gamma. Dari penelitian memperlihatkan bahwa mayoritas perawat mengalami stres kerja dalam kategori ringan, yakni sejumlah 22 responden (53,7%). Sedangkan, kinerja perawat sebagian besar tergolong baik, sejumlah 30 responden (73,2%). Analisis statistik menghasilkan nilai Gamma senilai -0,649, mengindikasikan hubungan sedang hingga kuat. Selain itu, nilai p-value senilai 0,030, lebih rendah dari tingkat signifikansi 0,05, memperlihatkan bahwa hubungan tersebut signifikan secara statistik. Berdasarkan hasil penelitian, dapat disimpulkan bahwa stres kerja terdapat hubungan signifikan dengan kinerja perawat di IGD, ICU, dan ruang rawat inap anak. Kata Kunci: Stres Kerja, Kinerja Perawat, Instalasi Gawat Darurat (IGD), Intensive Care Unit (ICU), Ruang Rawat Inap Anak.